PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, GOOD CORPORATE GOVERNANCE, DAN LEVERAGE TERHADAP PENGUNGKAPAN ISLAMIC SOCIAL REPORTING PERBANKAN SYARIAH DI INDONESIA PERIODE 2011-2014 - Siska Rukmanawatik (EPI 16 UMY 123, 2016)
Islamic Social Reporting (ISR) is a report of social responsibility which is in accordance with Islamic principles. In this context, Islamic banking as a research object. This research aims to discover and analyze the factors that effected the ISR disclosurewere company size, profitability, good corporate governance and leverage. The total samples of the research were nine public Islamic banking in Indonesia which were selected using purposive sampling technique. The result of the research showed that the company size and good corporate governance had significant effect on the ISR disclosure, while profitability and leverage were not significant effect the ISR disclosure on Islamic banking in Indonesia. Keywords: Islamic Social Reporting, firm size, profitability, good corporate governance, leverage, Islamic banking